The Transmission Chain Analysis of 2014–2015 Ebola Virus Disease Outbreak in Koinadugu District, Sierra Leone: An Observational Study - Muoghalu, Ifeanyi-Stanley; Moses, Francis; Conteh, Ishata; Swaray, Patrick; Ajudua, Anthonia; Nordström, Anders (Frontiers in Public Health, 2017)
Introduction Sierra Leone experienced an unprecedented Ebola virus disease (EVD) outbreak in all its districts. Koinadugu District was the last to report an EVD case. Several outbreak response strategies were implemented. As part of lessons learnt, we conducted an observational study to describe the transmission chain in the district and the impact of the control measures implemented to contain the outbreak. Methods We reconstructed the transmission chain, positioning both confirmed and probable cases, described the distribution of the EVD confirmed cases in the context of the routes of transmission (Community, Funeral or Health facility setting) and assessed the impact of control measures using the surveillance data collected during the outbreak. Results All 142 confirmed and probable EVD cases registered were fully resolved in the transmission chain. 72.5% of all the EVD cases in the district were exposed in the community, 26.1% exposed during funerals, and 1.4% exposed in the health facility setting. Health-care workers contributed little to the EVD outbreak. 71.1% of EVD transmission occurred among family members. Female EVD cases generated more secondary cases than their male counterparts (P = 0.03). With removal of EVD cases from the community and admission to the community care center (CCC), the EVD transmission in the community decreased to substantially lower rates. In addition, transmission due to exposure in health facilities was further reduced with the implementation of full infection and prevention controls. Conclusion This study details the transmission chain of EVD in a rural district setting and the public health interventions implemented to successfully limit the outbreak to just one of 11 chiefdoms. Heightened community-based surveillance for early case detection, swift isolation of suspect cases, efficient contact tracing and monitoring, and good infection prevention and control measures in health facilities were highly effective in limiting transmission and, eventually, breaking the transmission chain. CCCs were also instrumental in achieving early isolation and basic care for suspect cases, while ensuring that their family members who were close contacts remained in the community for easy contact tracing and monitoring. These were very useful lessons learnt that would inform the management of future outbreaks.